Religious Tolerance in War Takjil Content on TikTok @eloardoaruanse: A Virtual Ethnographic Study - Puspitasari, Euis Evi; Tiur Maida, Marcellista; Kurniadi, Endrian (Jogjakarta Communication Conference (JCC), 2025)
The